The Influence of Peer Corrective Feedback (PCF) on Students' Writing Skills in Hortatory Exposition Text - Gaffar, Muhammad Andriana; Fadilah, Dinda Fadilah; Nopita, Diana (JEELS (Journal of English Education and Linguistics Studies), 2024)
This study aims to determine the influence of peer corrective feedback (PCF) treatment on students' writing skills in the hortatory exposition text of grade XI in the second semester of vocational high school. This research used a quasi-experiment with a non-equivalent pre-test and post-test control group design. The data were collected from forty-three students from the experimental and control groups through observation, tests including pre-test and post-test, and treatment through feedback responses and PCF form for the experimental class. The data were analyzed by using a paired sample t-test to compare the writing skills in each of the two classes, and an independent sample t-test to determine the influence of peer corrective feedback on students’ writing skills. The paired sample t-test indicated a significant difference in writing skills between both classes. The independent sample t-test showed that peer corrective feedback positively influenced students' writing, helping with the correction and revision process, as a result, it is improving their hortatory exposition writing skills. It also enhanced their learning experience and motivation in the classroom as it was supported by more interactive and communicative learning through a collaborative learning environment.